Penyelesaian Sengketa Perdagangan Internasional melalui Mekanisme WTO sebagai Bentuk Peluang dan Tantangan bagi Indonesia serta Dasar Pengembangan Arah Reformasi - Danette Graciele Kosasih (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This paper examines the mechanisms of international trade dispute settlement under the World Trade Organization (WTO), focusing on how Indonesia navigates the system established by the Dispute Settlement Understanding (DSU). The analysis begins by outlining the DSU’s institutional design, which emphasizes compulsory jurisdiction, a rule-based adjudicatory process, and enforceable remedies aimed at ensuring stability and predictability in global trade relations. Indonesia’s participation in the WTO dispute settlement forum demonstrates a dynamic engagement: it has appeared as complainant, respondent, and third party in various disputes, gaining both strategic experience and institutional learning. For developing countries such as Indonesia, the DSU offers meaningful opportunities, particularly through its structured procedures, special and differential treatment provisions, and the ability to challenge trade barriers imposed by more powerful economies. However, Indonesia continues to face structural and procedural constraints, including limited technical expertise, resource-intensive litigation processes, and internal coordination challenges among domestic agencies. These obstacles hinder Indonesia’s ability to fully utilize the DSU as a tool for defending national trade interests. Against this backdrop, the urgency of DSU reform becomes increasingly evident, especially in light of the Appellate Body’s paralysis and the growing complexity of global trade. This paper argues that reforms should prioritize restoring a functioning appellate mechanism, strengthening provisions for developing countries, and enhancing transparency and procedural efficiency. Such reforms are essential not only for improving the legitimacy of the WTO system but also for enabling Indonesia and other developing members to participate more effectively in resolving international trade disputes.